2003
DOI: 10.1210/jc.2002-021890
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter Proteins (GLUT) in Human Endometrium: Expression, Regulation, and Function throughout the Menstrual Cycle and in Early Pregnancy

Abstract: An adequate endometrial glucose metabolism, mediated by facilitative glucose transporter molecules (GLUT), is an essential part of endometrial differentiation and decidualization to provide a nutritional and receptive milieu. In human endometrium, only the GLUT1 and GLUT3 isoforms are expressed, whereas glucose transporters, involved in insulin-dependent glucose uptake (GLUT2, GLUT4, GLUT8), could not be detected. Messenger RNA expression, analyzed by RNase protection assay, of both isoforms increased in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 38 publications
7
96
0
4
Order By: Relevance
“…A study of GLUT expression in immature rat uterus only detected the presence of GLUT1 and GLUT4 isoforms (Welch & Gorski 1999), while in the human endometrium only GLUT1 and GLUT3 have been reported (Younes et al 1997, von Wolff et al 2003. In Ishikawa endometrial cancer cells we detected the expression of GLUT1-4 and GLUT6.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A study of GLUT expression in immature rat uterus only detected the presence of GLUT1 and GLUT4 isoforms (Welch & Gorski 1999), while in the human endometrium only GLUT1 and GLUT3 have been reported (Younes et al 1997, von Wolff et al 2003. In Ishikawa endometrial cancer cells we detected the expression of GLUT1-4 and GLUT6.…”
Section: Discussionmentioning
confidence: 70%
“…The normal human endometrium expresses GLUT1 and GLUT3 and the expression of mRNA and protein of these transporters is increased in the secretory phase of the menstrual cycle when estrogen and progesterone levels are high (von Wolff et al 2003). The normal rat uterus expresses GLUT1 and GLUT4.…”
Section: Introductionmentioning
confidence: 99%
“…Because other GLUTs were demonstrated to have expression in endometrium, [27][28][29][30] and because GLUT8 appeared to be hormonally regulated, 27,30,31 we hypothesized that GLUT1 and GLUT8 would be overexpressed in endometrial cancer compared to benign endometrial tissue, controlled for menopausal status. As with the upregulation of glucose transporters in other cancers, the upregulation of GLUT1 and GLUT8 may identify poorly differentiated, thus more aggressive endometrial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, von Wolff et al 30 analyzed endometrial tissue for GLUT8 by northern blot analysis and found no GLUT8 mRNA expression. The reason(s) for these differing results is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin gene expression is also influenced by E 2 levels. At proestrus, when estrogen levels peak, insulin mRNA expression is decreased in the pancreas (4), and in the luteal phase of the cycle, the expression of some glucose transporters (GLUTs) in the uterus are also affected (5).…”
Section: Muscle Glut4 Regulation By Estrogen Receptors Er␤ and Er␣mentioning
confidence: 99%